Anti-Hepatocellular Carcinoma Effects of the Chloroform Root Extract of Burm - Peter Waziri BSc, MSc, PhD; Richard Auta BSc, MSc, PhD; Mustapha U Imam MBBS, MSc, PhD; Ben A Chindo BPharm, MSc, PhD; Zakari Ladan BSc, MSc, PhD; Zainab Mohammed BSc, MSc, PhD; Samson Wayah BSc, MSc, PhD; Ja'afar Mohammed BSc, MSc, PhD; Mohammed I Tahir BSc, MSc, PhD; Abdurrahman E Ahmad BSc, MSc, PhD; Yusuf Alhassan BSc; Daniel Tyoapine BSc; et al. (SAGE Publishing, 2024)
Liver cancer is the most common cancer among males in Africa. The disease has a poor prognosis and its treatment is associated with toxicity and resistance. For this reason, numerous herbal combinations are being subjected to anticancer screening to circumvent the shortcomings of the conventional anticancer drugs. In the current study, the in vivo anti-cancer effects of the chloroform root extract of the herb, Clausena excavata Burm were investigated. Liver cancer was induced in mice by a single intraperitoneal injection of diethylnitrosamine (DEN) followed by oral administration of the promoter of carcinogenesis, 2-aminoacetyl fluorine that was mixed with the mice feed. The cytotoxicity of the root extract of C. excavata on liver cancer cells was investigated using liver enzyme, histology, DNA fragmentation and caspases assays. Real time qPCR was conducted to evaluate the effect of the extract on apoptotic genes. The findings revealed that the extract of C. excavata significantly decreased the progression of hepatocarcinogenesis and the toxicity-induced production of the liver enzymes, alanine and aspartate aminotransferases. The histological analyses of the liver tissues revealed evidence of apoptotic cell death. The extract also provoked significant ( p  < .05) expressions of caspase 9 protein and gene as well as other apoptotic genes (P53, P27, Apaf-1, cytochrome C, bax and bid). Therefore, we postulate that the chloroform root extract of C. excavata induces apoptosis of liver cancer in mice.